Potential costs of veterans' health care. - Golding, Heidi L. W.; United States. Congressional Budget Office ([Washington, D.C.] : Congress of the United States, Congressional Budget Office, 2010)
"This Congressional Budget Office (CBO) report--which was mandated by section 104 of the Consolidated Appropriations Act, 2008 (Public Law 110-161)--examines prospective demands on VA's health care system and the potential budgetary implications of meeting veterans' health care needs over the 2011-2020 period. CBO projects the potential costs to treat all veterans enrolled in VA's health care system and also, separately, projects the potential costs to treat veterans returning from the military operations in Iraq and Afghanistan and related activities."--Preface
The health care program of the Department of Veterans Affairs -- Potential costs of providing health care to all enrolled veterans -- Potential costs of providing health care to veterans of overseas contingency operations.
"Pub. no. 4045."
Shipping list no.: 2011-0066-P.
"A CBO report."
"October 2010."
"The report was prepared by Heidi Golding of CBO's National Security Division"--Pref.
Includes bibliographical references.
Keywords: United States. -- Dept. of Veterans Affairs -- Appropriations and expenditures; Veterans -- Medical care -- United States -- Costs -- Forecasting